Monitoring of socio-economic development of Omsk region and adaptation processes - P. V. Ruzanov (Омский научный вестник: Серия "Общество. История. Современность", 2019)
The problem and the goal. The depressed state of the economy makes the adaptation processes activate. The purpose of the article is to study the factors of adaptation processes in Omsk region, the selection of signs of adaptation. Signs of adaptation is the movement of labor: the departure of the list of employees, the balance of migration flows. Methods. The article uses an analytical method. In particular, indicators of the standard of living of the population, such as real money income, consumer spending, expenditure structure, unemployment, etc., are analyzed. Comparison is made with national and federal indicators. Analysis and assessment of the socio-economic situation of the region involves the definition of the relationship with adaptation processes. Results. The analysis revealed the conditions of adaptation processes in Omsk region, factors that are the causes, driving forces of the adaptation process, determining its character or its individual features. Findings. The economy of Omsk region can be characterized as depressed, since the considered indicators of living standards lag behind the all-Russian and federal indicators. In Omsk region, adaptive processes are more developed than in other regions